Prevalence and Determinants of Anxiety and Depression Among Healthcare Workers in Liaoning Province, China - Lu J; Dou X; Yi Y; Yu Y; Zhou L (Dove Medical Press, 2024)
Jiachen Lu, Xiaofeng Dou, Yaohui Yi, Yingying Yu, Ling Zhou School of Public Health, Dalian Medical University, Dalian, People's Republic of ChinaCorrespondence: Ling Zhou, Email zhouling0609@163.comPurpose: To assess the anxiety and depression and their predictors among healthcare workers in Liaoning Province, China.Methods: In order to explore the influencing factors and prevalence of anxiety and depression among healthcare workers, a cross-sectional research design was used to survey 500 healthcare workers using the 14-item Hospital Anxiety Depression Scale (HADS), the Rosenberg Self-Esteem Scale (RSES), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Survey of Perceived Organizational Support (SPOS).Results: About 47.12% of the healthcare workers suffered from anxiety and 71.63% suffered from depression. In our study, we found that the health status (OR: 0.540, 95% CI: 0.298- 0.976), self-esteem (OR: 0.395, 95% CI: 0.251- 0.619), PSS (OR: 0.621, 95% CI: 0.388- 0.994), organizational support (OR: 0.533, 95% CI. 0.333- 0.854) were protective factors for healthcare workers suffering from anxiety, and resistance to COVID-19 (OR: 1.703, 95% CI: 1.082- 2.681) was a risk factor for healthcare workers suffering from anxiety, while good quality of life (OR: 0.385, 95% CI: 0.206- 0.719) self-esteem (OR: 0.187, 95% CI: 0.110- 0.317), and PSS (OR: 0.475, 95% CI: 0.267- 0.847) were protective factors for healthcare workers suffering from depression, and at the age of 35- 40 years (OR: 2.475, 95% CI: 1.140- 5.369) and resistance to COVID-19 (OR: 2.219, 95% CI: 1.313- 3.751) were risk factors for healthcare workers suffering from depression.Conclusion: The anxiety and depression status of healthcare workers in China is poor, and hospital administrators should take positive measures to support healthcare workers and give positive expectations to alleviate negative emotions such as anxiety and depression.Keywords: anxiety, depression, cross-sectional study, healthcare workers